Optimization of Computer Network Security System Against Malware Attacks Using Firewall Filtering with Port Blocking Method - Andri Andri; Indra Gunawan; Ika Okta Kirana (JOMLAI: Journal of Machine Learning and Artificial Intelligence, 2022)
Computer networks have an important role in teaching and learning activities in schools, but there are also negative impacts. One of them is prone to attack by malware such as viruses and so on, as is the case at the Satria Mandiri Private Vocational School in Bandar Huluan. So far, the computer network at the school is very easy to attack by malware. The negative impact of malware on the network is bandwidth traffic overload, causing bandwidth constraints to run out quickly or data transfer traffic to be slower than usual. The reliability of a network can be determined from the security factor of the network itself. Some routers have firewall settings that are quite capable but need to be managed more specifically based on the needs of the 1500 Kbps network scale and available bandwidth. Creating good rules in the firewall will make it easier to filter network traffic and bandwidth so that it can create security and convenience for network and bandwidth users. Port blocking allows users or users to interact with the proxy server on the local network, where the connected user has gone through verification that can filter malware activity with embedded rules